The girl who lived twice [compact disc, unabridged] - Lagercrantz, David; Larsson, Stieg, 1954-2004 (Millennium (Norstedts förlag)., 2019)
"Lisbeth Salander--the fierce, unstoppable girl with the dragon tattoo--has disappeared ... And no one is aware that at long last she's got her primal enemy, her twin sister, Camilla, squarely in her sights. Mikael Blomkvist is trying to reach Lisbeth. He needs her help unraveling the identity of a man who lived and died on the streets of Stockholm--a man who does not exist in any official records and whose garbled last words hinted at possible damaging knowledge of people in the highest echelons of government and industry. In his pocket was a crumpled piece of paper with Blomkvist's phone number on it. Once again, Salander and Blomkvist will come to each other's aid, moving in tandem toward the truths they each seek"--Container.